Tribal Life in India - Bose, Nirmal Kumar (New Delhi, 2002)
The book, Tribal Life In India looks at from close quarters various aspects of social, economic and cultural life of around 68 millions of our fellowmen who are considered to belong to the Scheduled Tribes. It also enlightens the readers on the varied means of their livelihood and also their social organisation, religion, art and music. Several observations made in the book are the outcome of the personal experiences of the author. The present volume has been supplemented by an exhaustive list of the Scheduled Tribes in India and their geographical locations. Written in a very simple language, the book would be quite useful for students of Anthropology, Sociology, Culture as well as general readers.
Keywords: Tribal -India